Teaching Non Science and Nonsense as Science! - Haque, Anwar Ul (International Journal of Pathology, 2018)
Human beings are bestowed with super intellectand astuteness along with capability of acquiring,retaining and reproducing all knowledge. Theangels who are manager of day to day affairs aremade to bow down and obey man. Man can conquerthe world but not the Satan, the rejected one!Indeed he can easily become its slave and thenSatan can use man’s intelligence, brain power,knowledge and “wisdom” for evil and destruction.The man by following satanic path reduceshimself to the lowest of the low and can do unbelievablefrauds based on absolute lies and fabrication!One of the most glaring examples of such isDarwinism and theory of evolution! Both of theseare not based on any solid scientific grounds andevidences! Their flaws are quite obvious but yetthese theories are widely accepted by many peoplethanks to powerful media and unified textbooksengaged in deliberately propagating outrightlies and deliberate fabrications